1999
DOI: 10.1161/01.cir.100.8.869
|View full text |Cite
|
Sign up to set email alerts
|

Aminorex, Fenfluramine, and Chlorphentermine Are Serotonin Transporter Substrates

Abstract: We speculate that medications that are 5-HT transporter substrates get translocated into pulmonary cells where, depending on the degree of drug retention, their intrinsic drug toxicity, and individual susceptibility, PPH could develop as a response to high levels of these drugs or metabolites. Emerging evidence suggests that it is possible to develop transporter substrates devoid of adverse side effects. Such medications could have therapeutic application in the management of obesity, drug dependence, depressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
134
0
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 194 publications
(143 citation statements)
references
References 32 publications
7
134
0
2
Order By: Relevance
“…SERTs play a major role in this process by allowing drugs to accumulate to high concentrations within cells. The validity of this hypothesis and its relevance to other adverse effects of FEN and dFEN in non-neural tissues (i.e., cardiac valvulopathy and pulmonary hypertension) remains to be determined (Rothman et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…SERTs play a major role in this process by allowing drugs to accumulate to high concentrations within cells. The validity of this hypothesis and its relevance to other adverse effects of FEN and dFEN in non-neural tissues (i.e., cardiac valvulopathy and pulmonary hypertension) remains to be determined (Rothman et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The profile of 5HT release caused by phentermine does not resemble that of a 5HT uptake inhibitor which, regardless of potency, would take much longer (1 -1.5 h 5,6 ) to maximally increase extracellular 5HT. In any event, phentermine has already been shown to be essentially inactive as a 5HT uptake inhibitor in vitro 14,17 (IC 50 ¼ 11 -14 mM). As for alternative mechanisms, although inhibition of monoamine oxidase (MAO) can yield relatively rapid elevations of extracellular 5HT, 18 these are usually persistent and can continue to rise for up to 5 h. 18,19 Again, however, phentermine has been shown to be extremely weak as an inhibitor of MAO A (IC 50 ¼ 100 -200 mM) 20,21 or MAO B (IC 50 ¼ 300 -900 mM).…”
Section: Discussionmentioning
confidence: 99%
“…These medications were removed from clinical use in 1997 due to the occurrence of CVD in some patients [67]. We reported that fenfluramine, aminorex, and other amphetaminerelated drugs known to increase the risk for developing PPH (e.g., chlorphentermine) share the common feature of being SERT substrates [68]. Our findings implicated SERT in the mechanism underlying fenfluramine-induced PPH.…”
Section: Adverse Effectsmentioning
confidence: 66%